PENENTUAN KAPASITOR PADA SELF EXCITED INDUCTION GENERATOR (SEIG) TIGA FASA UNTUK PENGOPERASIAN BEBAN SATU FASA DENGAN ALGORITMA KUNANG-KUNANG - Admin APERTI (Aliansi Perguruan Tinggi Badan Usaha Milik Negara (APERTI BUMN), 2018)
Self Excited Induction Generator (SEIG) is widely used in isolated area due to the ability to produce excitation indipendently without having to connect with the grid. Often SEIG operates as single phase to adjust load condition in isolated area. Three phase SEIG is able to operated as single phase, but this condition causes derating on the machine due to stator unbalance. This research proposed optimal sizing of excitation capacitor for three phase SEIG operated in single phase load. Optimal sizing of excitation capacitor is aimed to maximize SEIG capacity by considering operation limit of current and voltage stator. Firefly Algorithm (FA) is used to optimize capacitor size. Optimization result is verified through simulation on a three phase induction machine, 0.75kW , 380V, 50Hz, 4 poles. Simulation results show that proposed method is able to increased output power of SEIG up to 36%.